Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/hep.27654
|View full text |Cite
|
Sign up to set email alerts
|

High liver fibrosis index FIB‐4 is highly predictive of hepatocellular carcinoma in chronic hepatitis B carriers

Abstract: Screening for hepatocellular carcinoma (HCC) is clinically important given that its early detection has remarkable survival benefits. We investigated the possible role of FIB-4, a recently developed noninvasive marker for liver fibrosis based on routine laboratory tests, as a clinical indicator for predicting future HCC among hepatitis B surface antigen (HBsAg) carriers. Our retrospective cohort study involved 986 Korean HBsAg carriers 40 years of age or older who visited Seoul National University Hospital for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 40 publications
(74 reference statements)
3
85
1
Order By: Relevance
“…It has been revealed that there is a significant role of liver fibrosis on progression and metastasis of HCC, especially for patients who had comorbidity of HBV infection [20][21][22]. In the current study, we found the preoperative LSM value measured though FibroScan was an independent prognostic factor for HBV-related HCC patients.…”
Section: Discussionsupporting
confidence: 47%
“…It has been revealed that there is a significant role of liver fibrosis on progression and metastasis of HCC, especially for patients who had comorbidity of HBV infection [20][21][22]. In the current study, we found the preoperative LSM value measured though FibroScan was an independent prognostic factor for HBV-related HCC patients.…”
Section: Discussionsupporting
confidence: 47%
“…A cut-off value ≤1.45 could differentiate moderate from severe fibrosis with an NPV of 86%, a sensitivity of 71% and a specificity of 73%. A 2014 meta-analysis examined the value of the FIB-4 index (42,43). In clinical practice, the low cut-off of FIB-4 at 1.45 can be used to rule out patients without advanced fibrosis, hence it can be used as a triaging test (4).…”
Section: Fib-4 Indexmentioning
confidence: 99%
“…Subsequent studies also reported FIB-4 to be a strong indicator of liver cirrhosis [8,9]. Suh et al reported that in patients with chronic hepatitis B infection, high FIB-4 scores of >2.4 correlated with hepatocellular carcinoma incidence [10]. High FIB-4 was shown to be a strong predictor and risk factor for hepatocellular carcinoma in HIV-infected patients [6].…”
Section: Discussionmentioning
confidence: 98%